2019
DOI: 10.3389/fncel.2019.00509
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Induces Neuroinflammation and Mitochondrial Impairment in Mice Cerebral Cortex and Synaptic Fraction

Abstract: Brain mitochondrial dysfunction is involved in the development of neurological and neurodegenerative diseases. Mitochondria specifically located at synapses play a key role in providing energy to support synaptic functions and plasticity, thus their defects may lead to synaptic failure, which is a common hallmark of neurodegenerative diseases. High-Fat Diet (HFD) consumption increases brain oxidative stress and impairs brain mitochondrial functions, although the underlying mechanisms are not completely underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 50 publications
5
86
2
Order By: Relevance
“…The prefrontal cortex is important for executing inhibitory control (e.g., resisting strong appetite impulse), and neural responses in this area are significantly attenuated in obese individuals [ 41 , 42 ]. Cavaliere and colleagues [ 43 ] have revealed that inflammatory and oxidative stress markers such as TNF-α, IL-1β, and malondialdehyde were significantly elevated in synaptosomes in the cortex of obese mice fed a HFD for 18 weeks compared to those in a chow-fed lean control group. Antioxidant glutathione (GSH) was found to be markedly reduced, and the ratio of GSH to its oxidized form GSSG, a readout for antioxidant activity, was decreased, as expected in diet-induced obese mice.…”
Section: Mitochondrial Dysfunction In the Cnsmentioning
confidence: 99%
“…The prefrontal cortex is important for executing inhibitory control (e.g., resisting strong appetite impulse), and neural responses in this area are significantly attenuated in obese individuals [ 41 , 42 ]. Cavaliere and colleagues [ 43 ] have revealed that inflammatory and oxidative stress markers such as TNF-α, IL-1β, and malondialdehyde were significantly elevated in synaptosomes in the cortex of obese mice fed a HFD for 18 weeks compared to those in a chow-fed lean control group. Antioxidant glutathione (GSH) was found to be markedly reduced, and the ratio of GSH to its oxidized form GSSG, a readout for antioxidant activity, was decreased, as expected in diet-induced obese mice.…”
Section: Mitochondrial Dysfunction In the Cnsmentioning
confidence: 99%
“…We demonstrated that the beneficial effects exhibited by CLA isomers can be attributed to the activation of different regulatory pathways. Further experiments will be needed to investigate the different effects of dietary C9 or C10 supplementation in modulating cellular and mitochondrial ROS production [87][88][89] and to prevent oxidative DNA damage [90]. Moreover, additional experiments will be necessary for better investigating the involvement of additional genes metabolically linked to PPAR-α (i.e.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…In general, multi-organ damage due to inflammation and oxidative stress, hallmarks of both aging and obesity, highlight that these two processes are tightly interconnected [ 47 ]. The systemic impact of metabolic inflammation involves also the central nervous system [ 48 ]. The brain has been considered for a long time to be an organ protected from systemic inflammation by the blood–brain barrier, but more recent data indicate a tight association between obesity and neurodegeneration.…”
Section: Interplay Between Obesity and Aging: Inflammation And Neumentioning
confidence: 99%
“…HFD-dependent neuroinflammation and oxidative stress play a key role in the alteration of the BDNF levels not only in the hippocampus but also in several brain regions [ 48 , 99 , 100 , 101 ]. In particular, BDNF may be linked to neuroinflammation through NF-κB, although the exact regulatory mechanisms are not completely understood [ 91 , 102 ].…”
Section: Overnutrition and Synaptic Plasticitymentioning
confidence: 99%